Promoting hearing and cognitive health in audiologic rehabilitation for the well-being of older adults. - Sarant, Julia; Lemke, Ulrike; Giroud, Nathalie; Scherpiet, Sigrid; Weinstein, Barbara (International Journal of Audiology, 2024)
Objective: With our aging population, an increasing number of older adults with hearing loss have cognitive decline. Hearing care practitioners have an important role in supporting healthy aging and should be knowledgeable about cognitive decline and associated management strategies to maximize successful hearing intervention. Methods: A review of current research and expert opinion. Results: This article outlines the association between hearing loss and cognitive decline/dementia, hypothesized mechanisms underlying this, and considers current research into the effects of hearing intervention on cognitive decline. Cognition into old age, cognitive impairment, dementia, and how to recognize cognitive decline that is not part of normal aging are described. Screening of older asymptomatic adults for cognitive decline and practical suggestions for the delivery of person-centered hearing care are discussed. Holistic management goals, personhood, and person-centered care in hearing care management are considered for older adults with normal cognitive aging through to dementia. A case study illustrates important skills and potential management methods. Prevention strategies for managing hearing and cognitive health and function through to older age, and strategies to maximize successful hearing aid use are provided. Conclusion: This article provides evidence-based recommendations for hearing care professionals supporting older clients to maximize well-being through the cognitive trajectory.